Entre pincéis e livros: desenhando a trajetória de Julieta Carteado (1975-1994) - Ribeiro, Rejane Maria Rosa (2023)
Descriptive study, with a qualitative approach, which uses documentary research to analyze the trajectory of Julieta Carteado, in the period 1975-1994. The general objective of the study was: to narrate the trajectory of Julieta Carteado and her influence in the design of the cultural policy of the Central Library of the State University of Feira de Santana (UEFS); and specific objectives: to report the trajectory of Julieta Carteado in Librarianship and to identify Julieta Carteado's cultural production and actions, and her influence on the design of the cultural policy of the UEFS Central Library. Data collection was carried out through the documents of the Memorial Julieta Carteado and the archive of the UEFS Library System and through semi-structured interviews with relatives and servants of the Central Library. The results of the research showed that Julieta Carteado was a woman beyond her time, acting as an accountant, a profession exercised basically by men, had a higher education in Librarianship, training in stenography, English language, drawing and painting, an appreciable training for a black woman of the mid-twentieth century. At UEFS, he participated in administrative decisions through the two Councils, was responsible for the implementation of the Central Library and its director for ten years. It exerted a strong influence on the design of the Central Library's cultural policy through extensionist activities using cultural actions, which is a reference for other university libraries. He stood out in Librarianship, organizing libraries, participating in the Association and the Regional Council of Librarianship. He was active in the cultural life of Feira de Santana where he participated in several art exhibitions and was a member of the Christian Association and the Academia de Letras de Feira de Santana. Dealing with the trajectory of Julieta Carteado was to dialogue with memory, thus seeking support in the conceptions of Halbawachs (1990), Munaier (2015), Nora (1993), Pollak (1992) and Bosi (1979). It was through the memories of the research participants that narratives emerged that revealed Julieta's influence not only on the administration model adopted by the Library, on its cultural policy, but also the influence she exerted on the professional lives of those who knew her personally or through your story.